Determinants of Spike infectivity, processing, and neutralization in SARS-CoV-2 Omicron subvariants BA.1 and BA.2 - Pastorio, Chiara; Zech, Fabian; Noettger, Sabrina; Jung, Christoph; Jacob, Timo; Sanderson, Theo; Sparrer, Konstantin M.J.; Kirchhoff, Frank (Cell host & microbe, 2022)
SARS-CoV-2 Omicron rapidly outcompeted other variants and currently dominates the COVID-19 pandemic. Its enhanced transmission and immune evasion are thought to be driven by numerous mutations in the Omicron Spike protein. Here, we systematically introduced BA.1 and/or BA.2 Omicron Spike mutations into the ancestral Spike protein and examined the impacts on Spike function, processing, and susceptibility to neutralization. Individual mutations of S371F/L, S375F, and T376A in the ACE2-receptor-binding domain as well as Q954H and N969K in the hinge region 1 impaired infectivity, while changes to G339D, D614G, N764K, and L981F moderately enhanced it. Most mutations in the N-terminal region and receptor-binding domain reduced the sensitivity of the Spike protein to neutralization by sera from individuals vaccinated with the BNT162b2 vaccine and by therapeutic antibodies. Our results represent a systematic functional analysis of Omicron Spike adaptations that have allowed this SARS-CoV-2 variant to dominate the current pandemic. [Display omitted] •Omicron Spike residue changes of S371F/L, S373P, and S375F impair Spike function•Changes of Q954H and N969K in HR1 reduce, while that of L981F enhances, S-mediated infection•Omicron-specific mutations in the NTD and RBD of Spike reduce neutralization•N440K, G446S, E484A, and Q493R confer resistance to bamlanivimab or imdevimab The Omicron Spike protein contains numerous mutations thought to play key roles in the efficient spread and immune evasion of this currently dominating SARS-CoV-2 variant. Pastorio, Zech, and colleagues examined the impact of mutations characteristic of the BA.1 and/or BA.2 Omicron lineages on Spike function, processing, and susceptibility to neutralization.